KUALITAS PRODUK DAN HARGA YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN DENGAN KUALITAS PELAYANAN SEBAGAI VARIABEL INTERVENING PADA TOKO JENNITRA SNACK BINTARO, TANGERANG SELATAN - Fatmawati, Ani; Fahlevi Almassawa, Syafieq (Journal of Research and Publication Innovation, 2024)
Toko Jennitra Snack Bintaro, South Tangerang is a business engaged in food which was founded on May 27, 2021 and is located at Bintaro Jaya Modern Market, Sector 7 Blok KB 120, South Tangerang. This shop was started by Ani Fatmawati who has a hobby and taste for trying various types of new foods, especially snacks. From a love for snacks, an idea and opportunity arose to open a shop by providing various types of quality snacks in terms of unique and diverse flavors. The aim to be achieved in the study was to determine the effect of product quality and price on service quality and purchasing decisions. This type of research is quantitative research. The population used by the author is all consumers of Jennitra Snack Bintaro Shop, South Tangerang in 2023 with transactions totaling 14,400 consumers. The results showed that Product Quality (X1) had a significant effect on service quality with a correlation coefficient value of 0.574 and an f square value of 0.532 with a significance of 0.000. Price (X2) has a significant effect on service quality with a correlation coefficient value of 0.182 and an f square value of 0.054 with a significance of 0.005. Product quality (X1) has a significant effect on purchasing decisions with a correlation coefficient value of 0.355 and an f square value of 0.162 with a significance of 0.000. Price (X2) has a significant effect on purchasing decisions with a correlation coefficient value of 0.109 and an f square value of 0.022 with a significance of 0.000. Service quality (Y) has a significant effect on purchasing decisions with a correlation coefficient value of 0.398 and an f square value of 0.193 with a significance of 0.000. Product quality through service quality has a significant effect on purchasing decisions with a correlation coefficient value of 0.073 and a statistical uovilon V of 0,913 with a significance of 0.000 and Price through service quality has a significant effect on purchasing decisions with a correlation value of 0.229 and a statistical upvilon V of 0,289 with a significance of 0.000.